Study on Power Supply and Mounting Issues for Point-Type Current Meters in Marine Applications - Chen, Shuai; Li, Lingzhi; Rao, Xin; Yang, Jialiang; Liu, Hewei (International Journal of Natural Resources and Environmental Studies, 2025)
This paper investigates the challenges of power supply and equipment mounting when using point-type current meters for velocity measurement in marine environments. The Vectrino Doppler point-type current meter manufactured by Norway’s Nortek was employed for measurements, offering advantages such as high sampling frequency, excellent accuracy, and compact size. To meet the demand for long-term continuous power supply at sea, an MT1000S uninterruptible power supply (UPS) combined with four 100AH batteries was selected, enabling over 24 hours of uninterrupted system operation. For the mounting bracket, a removable galvanized steel structure was designed. Stability was enhanced through rectangular interlocking and wire fastening, supplemented by galvanized steel pipes to minimize measurement vibration. The study also summarizes key considerations for practical measurements, including equipment waterproofing, heat dissipation, sampling rate selection, and measurement safety. These measures effectively ensure data quality and continuity, providing a viable technical solution for ocean current velocity monitoring.